Prolonged dual antiplatelet therapy in selected patients with acute coronary syndrome. Issue 1 (7th January 2022) - Spirito, Alessandro; Mehran, Roxana
Key Points: It is crucial to identify patients with an increased bleeding or ischemic risk that may benefit from a tailored antiplatelet regimen. This study confirmed the benefit of a prolonged DAPT (≥12 months) in reducing ischemic events without bleeding harm in a real world East Asian population presenting with acute coronary syndrome and additional clinical and angiographic high‐risk features. An alternative approach, consisting of a prolonged P2Y12 monotherapy, is under investigation in this patient subset.